BIOSENSOR ELEKTROKIMIA BERBASIS POLIMER CETAK MOLEKULER (MIP) DAN CETAK PERMUKAAN UNTUK DETEKSI PENYAKIT INFEKSIUS: Tinjauan Kemajuan Terkini dan Tantangan dalam Pengembangan Biosensor Elektrokimia Berbasis MIP untuk Deteksi Patogen - Hudaiby, Nazwa; Ritonga, Winsyahputra (EINSTEIN (e-Journal), 2026)
Electrochemical biosensors have emerged as promising tools for the diagnosis of infectious diseases due to their high sensitivity, rapid response, and low cost. The use of molecularly imprinted polymers (MIPs) and surface imprinted polymers (SIPs) as robust and selective artificial receptors has gained significant attention. This review summarizes the recognition mechanisms between MIPs/SIPs and various infectious disease biomarkers, including small molecules, microbial toxins, viruses, and bacterial or fungal cells. Different MIP/SIP fabrication techniques such as electropolymerization, coating, and micro-contact imprinting are discussed. The review also highlights clinical applications of MIP/SIP-based biosensors for detecting specific pathogens, such as HPV, HIV, E. coli, and Zika virus. Key challenges such as enhancing sensitivity and selectivity, as well as the future potential of integrating artificial intelligence in biosensor design, are also addressed